Analysis of the agricultural insurance portfolio for the Iraqi National Insurance Company - MAJEED, MANAL HAMEED (The journal of contemporary issues in business and government, 2020)
The agricultural sector suffers from many risks and natural disasters, such as droughts and heavy rains that cause floods, as well as hail and agricultural pests, etc., that threaten agricultural activity and reduce it, which leads to the failure of farmers and peasants for fear of being subjected to continuous losses. Nevertheless, we notice almost complete reluctance to move towards agricultural insurance, due to the dependence of farmers on the government, which adopts the principle of compensation instead of agricultural insurance when natural disasters happen despite the difficulties and financial hardship as well as the suspicion of corruption that haunt the compensation process and this represents the most important problem for research In addition to the weakness of agricultural insurance With its current mechanisms and the absence of its own law that includes government support. The importance of the study is highlighted through the role of agricultural insurance in continuing to secure farmers ’income and ensuring food access to the citizen, as it is a true contributor to reducing agricultural risks. The research aims to analyze the current reality to find new frameworks by proposing a draft law on agricultural insurance and establishing a fund for managing agricultural risks that will be a substitute for the law in the event that it is not legislated or because of the delay in the legislative procedures of the law. The research reached several conclusions, the most important of which is the absence of a law on agricultural insurance, in addition to the absence of any government support for this activity other than global experiences. Several recommendations were presented, the most important of which are:The necessity of having a strategy for agricultural insurance that includes government support for insurance premiums of no less than 30% and the establishment of a Shareholding company consisting of the public and private sectors, In addition to forming of specialized committees to establish a partnership between farmers and the Ministry of Agriculture to raise awareness of this type of insurance.